Loss of sonic hedgehog gene leads to muscle development disorder and megaesophagus in mice. Issue 10 (16th May 2018) - Jia, Xueting; Min, Li; Zhu, Shengtao; Zhang, Shutian; Huang, Xiaofeng
ABSTRACT: Sonic hedgehog ( Shh ) is crucial for organogenesis in the foregut. This study investigated the function of Shh at the late‐gestational stage; during which, the esophagus continues to differentiate. We established cytokeratin 14 ( CK14 ) ‐Cre;Shh fl/fl mice in which the down‐regulation of Shh in the epithelium occurred at approximately the same time as esophageal muscle conversion. Hematoxylin and eosin and immunohistochemical staining, with antibodies against keratin 14, Shh, patched 1 (Ptch1), Gli1, proliferating cell nuclear antigen (PCNA), α‐smooth muscle actin (αSMA), high‐molecular‐weight caldesmon (hCD), myogenin, paired box 7 (Pax7), β3‐tubulin, and protein gene product 9.5 (PGP9.5), was performed to detect specific tissue dysplasia. Organ culture was conducted in vitro, and total mRNA was extracted to determine the transcriptional dysregulation. The esophagus of CK14‐Cre; Shh fl/fl mice developed into an independent tube with an obvious dilatation at postnatal d 0.5. The number of cell layers and the expression of PCNA were decreased in mutant mice, compared with those in wild‐type mice. The expression of hCD declined progressively in the middle, distal, and lower esophageal sphincter levels of the mutant esophagus from embryonic d 17.5, compared with the expression in wild‐type littermates. Pax7 accumulation and myogenin reduction in mutant mice indicated that esophageal skeletal‐myoblast progression was blocked. RNA sequencing analysis revealed a significant down‐regulation of genes involved in proliferation and muscular motivation in CK14‐Cre;Shh fl/fl mice. Thus, loss of Shh at the late‐ gestational stage leads to megaesophagus with reduced proliferation and a muscle development disorder in mice. mice.—Jia, X., Min, L., Zhu, S., Zhang, S., Huang, X. Loss of sonic hedgehog gene leads to muscle development disorder and megaesophagus in mice. FASEB J. 32, 5703–5715 (2018). www.fasebj.org